2020
DOI: 10.1093/mnras/staa1769
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the inner density slope of massive galaxy clusters

Abstract: We determine the inner density profiles of massive galaxy clusters (M200 > 5 × 1014 M⊙) in the Cluster-EAGLE (C-EAGLE) hydrodynamic simulations, and investigate whether the dark matter density profiles can be correctly estimated from a combination of mock stellar kinematical and gravitational lensing data. From fitting mock stellar kinematics and lensing data generated from the simulations, we find that the inner density slopes of both the total and the dark matter mass distributions can be inferred rea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 68 publications
4
17
0
Order By: Relevance
“…In general, it is non-trivial to infer the DM distribution from observations (e.g. Kowalczyk et al 2013;Harvey et al 2018;Oman et al 2019;Genina et al 2020;He et al 2020) and it is important to test how these difficulties impact the inferred SIDM cross-section when isothermal Jeans modelling is applied to observations. This was recently done in the context of galaxy cluster observations by Sagunski et al (2020), who found that the inferred cross-section from isothermal Jeans modelling using mock observations of simulated clusters was in agreement with the crosssection used in the simulations.…”
Section: Discussion a N D O U T L O O Kmentioning
confidence: 99%
“…In general, it is non-trivial to infer the DM distribution from observations (e.g. Kowalczyk et al 2013;Harvey et al 2018;Oman et al 2019;Genina et al 2020;He et al 2020) and it is important to test how these difficulties impact the inferred SIDM cross-section when isothermal Jeans modelling is applied to observations. This was recently done in the context of galaxy cluster observations by Sagunski et al (2020), who found that the inferred cross-section from isothermal Jeans modelling using mock observations of simulated clusters was in agreement with the crosssection used in the simulations.…”
Section: Discussion a N D O U T L O O Kmentioning
confidence: 99%
“…To constrain q DM ðrÞ, one needs to carefully model the different contributions to the cluster total mass profile, coming from the stellar mass of member galaxies, the hot gas component, the BCG stellar mass, and dark matter (Sartoris et al 2020). Moreover, it is important to take into account the velocity anisotropy on the interpretation of the line-of-sight stellar velocity dispersion profile of the BCG (Schaller et al 2015;Sartoris et al 2020;He et al 2020). For these reasons, current measurements and interpretations of the asymptotic central slope of q DM ðrÞ in galaxy clusters appear to be controversial (e.g., Newman et al 2013a;Sartoris et al 2020;He et al 2020).…”
Section: Cluster Mass Distributionmentioning
confidence: 99%
“…Moreover, it is important to take into account the velocity anisotropy on the interpretation of the line-of-sight stellar velocity dispersion profile of the BCG (Schaller et al 2015;Sartoris et al 2020;He et al 2020). For these reasons, current measurements and interpretations of the asymptotic central slope of q DM ðrÞ in galaxy clusters appear to be controversial (e.g., Newman et al 2013a;Sartoris et al 2020;He et al 2020). 18 The NFW and Einasto profiles represent phenomenological models for cuspy dark halos motivated by numerical simulations.…”
Section: Cluster Mass Distributionmentioning
confidence: 99%
“…Alternative models of this universal profile have been proposed (e.g., Moore et al 1998;Ricotti et al 2007;Del Popolo 2010;Navarro et al 2004;Stadel et al 2009). The inner slope of the mass distribution might deviate from the NFW model because of several processes such as dynamical friction, central condensation of cooled gas, and active galactic nucleus (AGN) feedback (e.g., Blumenthal et al 1986;Martizzi et al 2012;Schaller et al 2015;Laporte & White 2015;Peirani et al 2017;He et al 2020). The external slope of the mass distribution in individual clusters might deviate from the NFW model depending on the mass accretion rate in the cluster outskirts (e.g., Diemer & Kravtsov 2014;More et al 2015;Vallés-Pérez et al 2020).…”
Section: Introductionmentioning
confidence: 99%